Glass solid electrolyte and lithium-ion battery

JP7933877B2Active Publication Date: 2026-10-13IDEMITSU KOSAN CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024539138
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-03
Filing Date
2023-07-31
Publication Date
2026-10-13
Estimated Expiration
2043-07-31

Smart Images

  • Figure 0007933877000002
    Figure 0007933877000002
  • Figure 0007933877000003
    Figure 0007933877000003
  • Figure 0007933877000004
    Figure 0007933877000004
Patent Text Reader

Abstract

The present invention provides a glass solid electrolyte that contains, as constituent elements, lithium, phosphorus, sulfur, and a halogen which includes at least bromine, wherein the molar ratio (Li / P) of lithium (Li) to phosphorus (P) is 2.0-5.3, the molar ratio (S / P) of sulfur (S) to phosphorus (P) is 2.0-4.5, the molar ratio (X / P) of halogen (X) to phosphorus (P) is 0.7-2.3, and a peak derived from lithium bromide is exhibited in a powder X-ray diffraction using CuKα rays.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a glass solid electrolyte and a lithium-ion battery. [Background technology]

[0002] To improve the performance of lithium-ion batteries, it is important to increase the packing density (compactness) of the solid electrolyte powder. Mechanically softening the solid electrolyte (making it more easily compressible) is an effective way to improve the packing density.

[0003] In lithium-ion conductive sulfide solid electrolytes, glassy solid electrolytes generally have a high packing density due to their softness. Among these, Li3PS4 glass is known to have a high packing density. Solid electrolytes containing Li3PS4 glass are disclosed, for example, in Patent Documents 1 to 3. However, the Li3PS4 glass had a low ionic conductivity of less than 1 mS / cm. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Patent No. 5349427 [Patent Document 2] Patent No. 5521899 [Patent Document 3] Patent No. 5757284 [Overview of the project]

[0005] The object of the present invention is to provide a glass solid electrolyte that has a packing density equal to or greater than that of conventional glass solid electrolytes, and also has high ionic conductivity.

[0006] The present invention provides the following glass solid electrolytes, etc. 1. Containing lithium, phosphorus, sulfur, and halogens including at least bromine as constituent elements, The molar ratio (Li / P) of the lithium (Li) to the phosphorus (P) is 2.0 to 5.3, The molar ratio (S / P) of the sulfur (S) to the phosphorus (P) is 2.0 to 4.5, The molar ratio (X / P) of the halogen (X) to the phosphorus (P) is 0.7 to 2.3, A glass solid electrolyte that exhibits a peak derived from lithium bromide in powder X-ray diffraction using CuKα rays. 2. The glass solid electrolyte according to 1, wherein the crystallite size calculated from the peak half-value width of the peak with the maximum intensity among the peaks derived from the lithium bromide is 3 to 60 nm. 3. The halogen contains iodine, The glass solid electrolyte according to 1 or 2, which exhibits a peak derived from lithium iodide in powder X-ray diffraction using CuKα rays. 4. The glass solid electrolyte according to 3, wherein the crystallite size calculated from the peak half-value width of the peak with the maximum intensity among the peaks derived from the lithium iodide is 3 to 60 nm. 5. The glass solid electrolyte according to any one of 1 to 4, wherein the relative density of a 400MPa green compact is 90% or more. 6. The true density is 2.0 to 3.0 g / cm 3 The glass solid electrolyte according to any one of 1 to 5, which is as defined above. 7. The glass solid electrolyte according to any one of 1 to 6, wherein the molar ratio (X / P) is more than 0.75. 8. The glass solid electrolyte according to any one of 1 to 6, wherein the molar ratio (X / P) is more than 0.86. 9. The halogen contains iodine, The molar ratio (I / P) of the iodine (I) to the phosphorus (P) is 2.0 or less, The glass solid electrolyte according to any one of 1 to 8, wherein the molar ratio (Br / P) of the bromine (Br) to the phosphorus (P) is 0.01 to 1.5. 10. The glass solid electrolyte according to any one of 1 to 9, which has an ionic conductivity of 1 mS / cm or more. 11. A lithium ion battery comprising the glass solid electrolyte according to any one of 1 to 10. 12. A combination of two or more compounds or elements containing lithium, phosphorus, sulfur, and a halogen containing at least bromine as constituent elements, A method for producing a glass solid electrolyte, comprising vitrifying a mixture prepared by adjusting the molar ratio of lithium (Li) to phosphorus (P) (Li / P) to 2.0 to 5.3, the molar ratio of sulfur (S) to phosphorus (P) (S / P) to 2.0 to 4.5, and the molar ratio of halogen (X) to phosphorus (P) (X / P) to 0.7 to 2.3.

[0007] According to the present invention, a glass solid electrolyte can be provided that has a packing density equal to or greater than that of conventional glass solid electrolytes, and also has high ionic conductivity. [Brief explanation of the drawing]

[0008] [Figure 1] This is a schematic diagram illustrating a pellet density measuring device. [Figure 2] These are the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 1-4. [Figure 3] These are the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 5-8. [Figure 4] These are the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 9-13. [Figure 5] These are the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 14 and 15. [Figure 6] These are the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 16-18. [Figure 7] This is the X-ray diffraction pattern of the glass solid electrolyte prepared in Example 19. [Figure 8] These are the X-ray diffraction patterns of the glass solid electrolytes prepared in Comparative Examples 1 to 8. [Figure 9] These are the X-ray diffraction patterns of the glass solid electrolytes prepared in Comparative Examples 9 and 10. [Modes for carrying out the invention]

[0009] Embodiments of the present invention will be described below. In this specification, the upper and lower limit values ​​related to the numerical ranges indicated by "greater than or equal to," "less than or equal to," and "~" can be any combination of values, and the values ​​in the examples can also be used as the upper and lower limit values.

[0010] A glass solid electrolyte according to one embodiment of the present invention contains lithium (Li), phosphorus (P), sulfur (S), and a halogen (X) containing at least bromine as constituent elements. The molar ratio of the above constituent elements to phosphorus ((Li,S,X) / P) satisfies the following range. Li / P = 2.0~5.3 S / P = 2.0 ~ 4.5 X / P = 0.7~2.3

[0011] Furthermore, powder X-ray diffraction using CuKα radiation shows a peak originating from lithium bromide. The glass solid electrolyte of this embodiment has a higher halogen content compared to conventional glass solid electrolytes. As a result, a glass solid electrolyte with a packing density equal to or higher than that of conventional glass solid electrolytes and high ionic conductivity can be obtained. For example, a glass solid electrolyte can be obtained in which the relative density of the 400 MPa compacted powder, which is an indicator of packing density, is 90% or higher.

[0012] In this application, "glass solid electrolyte" refers to a solid electrolyte containing a glass (amorphous) component. The presence of a glass component can be confirmed by the presence of a broad peak (halo pattern) caused by the amorphous component in X-ray diffraction (XRD) measurements. In XRD measurements of glass solid electrolytes, some peaks originating from crystalline components or from the raw materials may also be observed.

[0013] In one embodiment, the molar ratio of lithium (Li) to phosphorus (P) (Li / P) is preferably 3.0 to 5.25, more preferably 3.5 to 5.20, and may also be 3.8 to 5.0, or even 4.0 to 4.8. Furthermore, the molar ratio of sulfur (S) to phosphorus (P) (S / P) is preferably 3.0 to 4.4, more preferably 3.5 to 4.3, and may also be 3.8 to 4.2, or even 3.9 to 4.1. Adjusting the molar ratio of sulfur to phosphorus within the above range has the effect of reducing the amount of hydrogen sulfide generated in low dew point environments. Furthermore, the molar ratio of halogen (X) to phosphorus (P) (X / P) is preferably 0.75 to 2.5, more preferably 0.80 to 2.3, and may also be 0.85 to 2.0, 0.90 to 1.8, or even 0.95 to 1.5.

[0014] The glass solid electrolyte of this embodiment contains bromine and halogens other than bromine, such as fluorine, chlorine, and iodine, as constituent elements. The molar ratio of bromine (Br) to halogen (X) (Br / X) is preferably 0.05 to 1.0, and more preferably 0.1 to 0.8. Furthermore, the molar ratio of bromine (Br) to phosphorus (P) (Br / P) is preferably 0.05 to 2.0, more preferably 0.1 to 1.5, and may also be 0.2 to 1.4, 0.3 to 1.3, or even 0.5 to 1.0.

[0015] In one embodiment, the halogen (X) includes bromine and iodine. Furthermore, the molar ratio of iodine (I) to phosphorus (P) (I / P) is preferably 2.0 or less, more preferably 0.1 to 1.5, and may also be 0.2 to 1.4, 0.3 to 1.3, or even 0.5 to 1.0.

[0016] The types and molar ratios of constituent elements in a glass solid electrolyte can be determined, for example, by an ICP emission spectrometer. The molar ratio of the constituent elements of a glass solid electrolyte can be adjusted by controlling the raw material composition. The molar ratio of the constituent elements in the raw materials is approximately equal to the molar ratio of the constituent elements in the resulting glass solid electrolyte.

[0017] In the glass solid electrolyte of this embodiment, it is preferable that the above molar ratio (Li / P) and the above molar ratio (X / P) satisfy the following formula (1). Li / P = (3±α) + X / P (1) (In the formula, α is between 0 and 0.5.)

[0018] By satisfying equation (1), the PS4, which is the main backbone of the glass solid electrolyte, 3- Because the amount of tetrahedral structure produced increases, it has the effect of reducing the amount of hydrogen sulfide generated in low dew point environments. Also, PS4 3- The P2S6 is larger and more rigid than its structure. 4- Structure and P2S7 4- Because the amount of structure formation is reduced, the softness of the glass solid electrolyte is improved. In equation (1), α may be between 0 and 0.3, between 0 and 0.1, or even 0.

[0019] In one embodiment, the true density of the glass solid electrolyte is 2.0 to 3.0 g / cm³. 3 It is preferable that the true density is within the above range, which means that the Li3PS4 glass contains a certain amount of halogen, and that halogen imparts softness to the solid electrolyte and improves the ionic conductivity compared to Li3PS4 glass. The true density of glass solid electrolytes is 2.05–2.9 g / cm³. 3 It is more preferable that the concentration be 2.1-2.8 g / cm³. 3 It is particularly preferable that this be the case. The true density of a glass solid electrolyte can be measured, for example, by a gas-phase displacement method using He gas. Details of the method for measuring the true density of a glass solid electrolyte are shown in the examples.

[0020] In one embodiment, the glass solid electrolyte exhibits diffraction peaks of lithium halides, such as lithium iodide, in addition to lithium bromide, as measured by powder X-ray diffraction using CuKα rays. The lithium halides observed in the powder X-ray diffraction measurement of the glass solid electrolyte have lower crystallinity than the lithium halide raw material. The presence of lithium halide diffraction peaks adds further softness to the mechanical softness of the glass solid electrolyte itself. Among the peaks originating from lithium halides, the peak with the maximum intensity is observed, for example, in the range where 2θ is 25-30° (deg). In one embodiment, the lithium halide is lithium iodide.

[0021] In one embodiment, the crystallite size calculated from the peak full width at half maximum of the peak with the highest intensity among the peaks derived from lithium bromide is 3 to 60 nm. Preferably, it is 5 to 50 nm, and more preferably, 7 to 40 nm. Generally, diffraction peaks in powder X-ray diffraction measurements have a width, and the width of the peak at half the peak height after subtracting the background is called the full width at half maximum (FWHM). It is known that there is a correlation between FWHM and crystallite size. As the crystallite size increases, the crystallinity increases and the repeating regularity of the crystal structure increases, so the FWHM of the diffraction peak in powder X-ray diffraction measurements becomes narrower.

[0022] Crystallite size can be adjusted by changing the composition. For example, crystallite size can be adjusted by changing the molar ratio of lithium (Li) to phosphorus (P) (Li / P), the molar ratio of bromine (Br) to halogen (X) (Br / X), and the molar ratio of iodine (I) to phosphorus (P) (I / P). When the solid electrolyte is in a glassy state, the full width at half maximum becomes extremely large, and the diffraction peaks become broadened.

[0023] Furthermore, in one embodiment, when there is a peak originating from lithium iodide, the crystallite size calculated from the peak full width at half maximum of the peak with the maximum intensity is 3 to 60 nm. Preferably, it is 5 to 50 nm, and more preferably, 7 to 40 nm.

[0024] The peak full width at half maximum and crystallite size are calculated from XRD. Details of the measurement and calculation methods are shown in the examples. The presence or absence of crystallites, i.e., whether or not LiBr and LiI peaks are observed, is also determined using the above calculation method. For example, the diffraction peak at 2θ = 28 ± 1° is used to calculate the peak width at half maximum (FWHM) for LiBr, and the diffraction peak at 2θ = 25.5 ± 1° is used for LiI.

[0025] The glass solid electrolyte of this embodiment has a packing density equal to or greater than that of conventional glass solid electrolytes, and also possesses high ionic conductivity. Specifically, the relative density of the 400 MPa compacted powder, which serves as an indicator of the filling rate, can be increased to 90% or higher. This relative density can also be increased to 90.5% or higher, or even 91% or higher. There is no particular upper limit on the relative density, but it is usually 99% or lower.

[0026] In this invention, the relative density of a 400 MPa compressed powder is the ratio of the density of the glass solid electrolyte powder when compressed at 400 MPa (referred to as pellet density) to the true density of the glass solid electrolyte (relative density (%) = pellet density × 100 / true density). A higher relative density means a higher packing efficiency. Details of the method for measuring the relative density of 400 MPa compacted powder are described in the examples.

[0027] Furthermore, the ionic conductivity of the glass solid electrolyte in this embodiment can be 1 mS / cm or higher, and can also be 1.1 mS / cm or higher.

[0028] The glass solid electrolyte of this embodiment can be manufactured, for example, by mixing the starting materials of a known lithium-ion sulfide solid electrolyte so that the molar ratio of the constituent elements satisfies a predetermined range, and then vitrifying the mixture.

[0029] As starting materials, two or more compounds or elements containing lithium, phosphorus, sulfur, and halogens as constituent elements can be used in combination, and there are no particular restrictions on which materials can be used as long as they exhibit ionic conductivity due to the metal atoms they contain.

[0030] Examples of the raw material containing lithium (Li) include lithium compounds such as lithium sulfide (Li₂S), lithium oxide (Li₂O), and lithium carbonate (Li₂CO₃), as well as simple lithium metal. Among these, lithium compounds are preferred, and lithium sulfide is more preferred.

[0031] The above lithium sulfide can be used without particular limitation, and high-purity lithium sulfide is preferred. Lithium sulfide can be produced, for example, by the methods described in JP 7-330312 A, JP 9-283156 A, JP 2010-163356 A, and JP 2011-84438 A.

[0032] Specifically, lithium hydroxide and hydrogen sulfide are reacted at 70°C to 300°C in a hydrocarbon-based organic solvent to generate lithium hydrosulfide, and then this reaction solution is subjected to dehydrogen sulfuration, whereby lithium sulfide can be synthesized (JP 2010-163356 A).

[0033] Further, lithium hydroxide and hydrogen sulfide are reacted at 10°C to 100°C in an aqueous solvent to generate lithium hydrosulfide, and then this reaction solution is subjected to dehydrogen sulfuration, whereby lithium sulfide can be synthesized (JP 2011-84438 A).

[0034] Examples of the raw material containing phosphorus (P) include phosphorus sulfides such as diphosphorus trisulfide (P₂S₃) and diphosphorus pentasulfide (P₂S₅), phosphorus compounds such as sodium phosphate (Na₃PO₄), and simple phosphorus. Among these, phosphorus sulfides are preferred, and diphosphorus pentasulfide (P₂S₅) is more preferred. Phosphorus compounds such as diphosphorus pentasulfide (P₂S₅) and simple phosphorus can be used without particular limitation as long as they are industrially produced and sold.

[0035] The raw material containing halogen (X) as a constituent element preferably contains, for example, a halogen compound represented by the following formula.

[0036] M l -X m In the formula, M represents sodium (Na), lithium (Li), boron (B), aluminum (Al), silicon (Si), phosphorus (P), sulfur (S), germanium (Ge), arsenic (As), selenium (Se), tin (Sn), antimony (Sb), tellurium (Te), lead (Pb), bismuth (Bi), or any of these elements bonded to oxygen or sulfur. Lithium (Li) or phosphorus (P) is preferred, and lithium (Li) is more preferred.

[0037] X is a halogen element selected from fluorine (F), chlorine (Cl), bromine (Br), and iodine (I).

[0038] Furthermore, l is an integer of 1 or 2, and m is an integer from 1 to 10. When m is an integer from 2 to 10, that is, when there are multiple X values, X may be the same or different. For example, in SiBrCl3, which will be discussed later, m is 4, and X consists of two different elements, Br and Cl.

[0039] Specifically, halogen compounds include sodium halides such as NaI, NaF, NaCl, and NaBr; lithium halides such as LiF, LiCl, LiBr, and LiI; boron halides such as BCl3, BBr3, and BI3; aluminum halides such as AlF3, AlBr3, AlI3, and AlCl3; silicon halides such as SiF4, SiCl4, SiCl3, Si2Cl6, SiBr4, SiBrCl3, SiBr2Cl2, and SiI4; phosphorus halides such as PF3, PF5, PCl3, PCl5, POCl3, PBr3, POBr3, PI3, P2Cl4, and P2I4; and SF2, SF4, SF6, and S2F 10Sulfur halides such as SCl2, S2Cl2, S2Br2; germanium halides such as GeF4, GeCl4, GeBr4, GeI4, GeF2, GeCl2, GeBr2, GeI2; arsenic halides such as AsF3, AsCl3, AsBr3, AsI3, AsF5; selenium halides such as SeF4, SeF6, SeCl2, SeCl4, Se2Br2, SeBr4; tin halides such as SnF4, SnCl4, SnBr4, SnI4, SnF2, SnCl2, SnBr2, SnI2; antimony halides such as SbF3, SbCl3, SbBr3, SbI3, SbF5, SbCl5; TeF4, Te2F 10 Examples include telluride halides such as TeF6, TeCl2, TeCl4, TeBr2, TeBr4, and TeI4; lead halides such as PbF4, PbCl4, PbF2, PbCl2, PbBr2, and PbI2; and bismuth halides such as BiF3, BiCl3, BiBr3, and BiI3.

[0040] Among these, lithium halides such as lithium chloride (LiCl), lithium bromide (LiBr), and lithium iodide (LiI), and phosphorus halides such as phosphorus pentachloride (PCl5), phosphorus trichloride (PCl3), phosphorus pentabromide (PBr5), and phosphorus tribromide (PBr3) are preferred. Of these, lithium halides such as LiCl, LiBr, and LiI, and PBr3 are preferred, lithium halides such as LiCl, LiBr, and LiI are more preferred, and LiI and LiBr are even more preferred.

[0041] The halogen compound may be one of the above compounds used alone, or two or more compounds may be used in combination. In other words, at least one of the above compounds can be used.

[0042] In this embodiment, the raw materials preferably include a lithium compound, a phosphorus compound, and a halogen compound containing at least bromine, wherein at least one of the lithium compound and the phosphorus compound contains a sulfur element, more preferably a combination of lithium sulfide, phosphorus sulfide, and two or more lithium halides, and even more preferably a combination of lithium sulfide, diphosphorus pentasulfide, and two or more lithium halides.

[0043] For example, when lithium sulfide, phosphorus pentasulfide, or two or more lithium halides are used as raw materials for a glass solid electrolyte, the molar ratio of lithium sulfide to phosphorus pentasulfide in the input raw materials is preferably 65-85:15-35, more preferably 70-80:20-30, even more preferably 72-78:22-28, and particularly preferably 75:25.

[0044] Furthermore, when the amount of Li3PS4 calculated from the constituent elements Li, P, and S of lithium sulfide and phosphorus pentasulfide is set to 100 mole parts, it is preferable to use 75 to 250 mole parts of lithium halide, more preferably 80 to 225 mole parts, and may also be 85 to 200 mole parts, 90 to 175 mole parts, or 95 to 150 mole parts.

[0045] In this embodiment, the above raw materials are reacted by applying mechanical stress to produce a glass solid electrolyte. Here, "applying mechanical stress" means applying mechanical shear force, impact force, etc. Means of applying mechanical stress include, for example, pulverizers such as planetary ball mills, vibratory mills, and rolling mills, as well as kneaders. The raw material powder is pulverized and mixed by strong mechanical stress until at least a portion of it can no longer maintain its crystallinity.

[0046] For grinding and mixing conditions, for example, if a planetary ball mill is used as the grinder, the rotation speed should be set to tens to hundreds of revolutions per minute, and the processing should be done for 0.5 to 100 hours. More specifically, in the case of the planetary ball mill used in the embodiment of this application (manufactured by Fritsch: model number P-5), the rotation speed of the planetary ball mill is preferably 100 rpm to 400 rpm, and more preferably 150 rpm to 300 rpm. The temperature during grinding may be room temperature, in which case external cooling is not performed, and for example, a 5-minute shutdown period may be set every hour. However, if the conditions do not involve crystallization during grinding, grinding may be performed with cooling without setting a shutdown period. If zirconia balls are used as the grinding media, their diameter is preferably 0.2 to 20 mm.

[0047] The glass solid electrolyte of this embodiment has a packing density equal to or greater than that of conventional glass solid electrolytes, and also possesses high ionic conductivity, making it suitable for use in batteries. It is particularly suitable when lithium is used as the conductive element. The glass solid electrolyte of this embodiment may be used in the positive electrode layer, the negative electrode layer, or the electrolyte layer.

[0048] A lithium-ion battery according to one embodiment of the present invention includes the glass solid electrolyte of the present invention described above. For example, an all-solid-state lithium-ion battery can be manufactured by using the glass solid electrolyte of the present invention instead of a liquid electrolyte.

[0049] All-solid-state lithium-ion batteries mainly consist of a positive electrode layer, a negative electrode layer, and an electrolyte layer, and the glass solid electrolyte of the present invention can be used in any of these layers. Each layer can be manufactured by known methods. For example, when used in a positive electrode layer and a negative electrode layer, a positive electrode composite material or a negative electrode composite material can be obtained by mixing and dispersing a positive electrode active material or a negative electrode active material in the glass solid electrolyte of the present invention. The positive electrode active material can be used without particular limitations as long as it can promote a battery chemical reaction involving the movement of lithium ions, which is preferably used in this embodiment as an element that exhibits ionic conductivity in relation to the negative electrode active material. Examples of positive electrode active materials that enable such insertion and removal of lithium ions include oxide-based positive electrode active materials and sulfide-based positive electrode active materials.

[0050] Preferred oxide-based cathode active materials include lithium-containing transition metal composite oxides such as LMO (lithium manganese oxide), LCO (lithium cobalt oxide), NMC (lithium nickel manganese cobalt oxide), NCA (lithium nickel cobalt aluminate), LNCO (lithium nickel cobalt oxide), and olivine-type compounds (LiMeNPO4, Me=Fe, Co, Ni, Mn).

[0051] Examples of sulfide-based cathode active materials include titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), and nickel sulfide (Ni3S2). In addition to the above-mentioned positive electrode active material, niobium selenide (NbSe3) and other materials can also be used. In this embodiment, the positive electrode active material can be used alone or in combination of multiple types.

[0052] As the negative electrode active material, any material that can promote a battery chemical reaction involving the movement of lithium ions, preferably caused by the lithium element, can be used without particular limitations. This includes elements preferably used as elements that exhibit ionic conductivity in this embodiment, metals that can form alloys with lithium elements, oxides thereof, and alloys of such metals with lithium elements. As such a negative electrode active material capable of lithium ion insertion and removal, any material known as a negative electrode active material in the battery field can be used without limitation.

[0053] Examples of such negative electrode active materials include metallic lithium, metallic indium, metallic aluminum, metallic silicon, metallic tin, and other metallic lithium or metals that can form alloys with metallic lithium, oxides of these metals, and alloys of these metals with metallic lithium.

[0054] The electrode active material used in this embodiment may have a coating layer on its surface. As materials for forming the coating layer, examples of ionic conductors include elements that exhibit ionic conductivity in the crystalline sulfide solid electrolyte used in this embodiment, preferably lithium nitrides, oxides, or composites thereof. Specifically, lithium nitride (Li3N), Li4GeO4, and other materials with Li4GeO4 as the main structure are examples of Li 4-2x Zn x Conductors having a lithicon-type crystal structure such as GeO4, and conductors having a Li3PO4-type skeletal structure, such as Li3PO4. 4-x Ge 1-x P x Conductors having a thiolysicone-type crystal structure such as S4, La2 / 3-x Li 3x Examples include conductors having a perovskite-type crystal structure such as TiO3, and conductors having a NASICON-type crystal structure such as LiTi2(PO4)3.

[0055] Also, Li y Ti 3-y O4(0 <y<3)、Li4Ti5O 12 Examples include lithium titanate such as (LTO), lithium metal oxides of metals belonging to Group 5 of the periodic table such as LiNbO3 and LiTaO3, and oxide-based conductors such as the Li2O-B2O3-P2O5 system, Li2O-B2O3-ZnO system, and Li2O-Al2O3-SiO2-P2O5-TiO2 system.

[0056] An electrode active material having a coating layer can be obtained, for example, by applying a solution containing various elements that constitute the material forming the coating layer to the surface of the electrode active material, and then firing the electrode active material after application at a temperature preferably between 200°C and 400°C.

[0057] Here, as the solution containing various elements, for example, a solution containing alkoxides of various metals such as lithium ethoxide, titanium isopropoxide, niobium isopropoxide, and tantalum isopropoxide may be used. In this case, as the solvent, an alcohol-based solvent such as ethanol or butanol, an aliphatic hydrocarbon solvent such as hexane, heptane, or octane, or an aromatic hydrocarbon solvent such as benzene, toluene, or xylene may be used. Furthermore, the above-mentioned adhesion can be achieved by immersion, spray coating, or other methods.

[0058] The firing temperature is preferably 200°C to 400°C, more preferably 250°C to 390°C, from the viewpoint of improving manufacturing efficiency and battery performance, and the firing time is usually about 1 minute to 10 hours, preferably 10 minutes to 4 hours.

[0059] The coverage rate of the coating layer is preferably 90% or more, more preferably 95% or more, and even more preferably 100%, based on the surface area of ​​the electrode active material, i.e., the entire surface is covered. The thickness of the coating layer is preferably 1 nm or more, more preferably 2 nm or more, with an upper limit of preferably 30 nm or less, and more preferably 25 nm or less.

[0060] The thickness of the coating layer can be measured by cross-sectional observation using a transmission electron microscope (TEM), and the coverage rate can be calculated from the thickness of the coating layer, elemental analysis values, and BET surface area.

[0061] Furthermore, the above-mentioned battery preferably uses a current collector in addition to the positive electrode layer, electrolyte layer, and negative electrode layer, and known current collectors can be used. For example, a layer coated with Au or the like, which reacts with the above-mentioned glass solid electrolyte, can be used. [Examples]

[0062] The present invention will be described in detail below based on examples. Embodiments of the present invention are not limited to these examples. The evaluation method for the glass solid electrolyte prepared in each example is as follows. (1) Powder X-ray diffraction (XRD) measurement The glass solid electrolyte powder prepared in each example was packed into a groove 20 mm in diameter and 0.2 mm deep by leveling it with a glass tool. The packed samples were measured using Kapton film for XRD, without exposure to air. The 2θ position of the diffraction peak was determined by Le Bail analysis using the XRD analysis program RIETAN-FP. Powder X-ray diffraction measurements were performed under the following conditions. Equipment used: BRUKER “D2 PHASER” Tube voltage: 30kV Tube current: 10mA X-ray wavelength: Cu-Kα ray (1.5418Å) Optical system: Concentration method Slit configuration: Solar slit 4°, divergence slit 1mm, Kβ filter (Ni plate) used. Detector: Semiconductor detector Measurement range: 2θ = 10⁻⁶⁰° (deg) Step size, scan speed: 0.05°, 0.05° / sec To confirm the existence of a crystal structure based on the measurement results, the peak positions were analyzed using the XRD analysis program RIETAN-FP. The baseline was corrected using an 11th-order orthogonal polynomial, and the peak positions were determined.

[0063] (2) Peak width at half maximum The peak width at half maximum (FWHM) was calculated using a peak at 2θ = 25.5 ± 1° for LiI and a peak at 2θ = 28 ± 1° for LiBr. In the range where the aforementioned peak exists (2θ = 24.5 to 26.5° or 2θ = 27 to 29°), the half-width parameter E was determined by minimizing the difference between the measured intensity (vertical axis value of the XRD pattern) and the calculated value described below. Let A be the ratio of the Lorentz function (0 ≤ A ≤ 1), B be the intensity correction value, C be the angle 2θ at which the intensity is maximum, D be the intensity angle (2θ) to be calculated, E be the full width at half maximum parameter, F be the background, and G be the measured intensity at the intensity angle (2θ) to be calculated. With variables A, B, C, E, and F, the difference H between the measured and calculated intensity values ​​was calculated for each intensity angle (2θ) using the following equation (3). H = G - {B × {A / (1 + (DC)}} 2 / E 2 ) + (1-A) × exp(-1 × (DC) 2 / E 2 )}+F} (3)

[0064] The above variables were determined by summing H in the range of 2θ = 24.5 to 26.5° or 2θ = 27 to 29°, and then minimizing the sum of H using the GRG nonlinearity method with the solver function of spreadsheet software (Excel, Microsoft). Using the obtained FWHM parameter E, the FWHM was calculated using the following equation (4). Half-width = E × 2 × (ln4) (1 / 2) (4) If the peak intensity is calculated to be zero, the full width at half maximum (FWHM) parameter cannot be calculated either. In this case, no peak exists, meaning that no peak originating from LiI or LiBr is shown, and it can be assumed that no crystallites exist.

[0065] (3) Crystallite size The full width at half maximum (FWHM) calculated using the above method was denoted as b. Furthermore, to compensate for the instrument-derived FWHM broadening, the FWHM was corrected using NIST standard Si (640d, crystallite size 525nm). The corrected instrument-derived FWHM was then denoted as B. correct Therefore, the corrected full width at half maximum (FWHM) β used to calculate the crystallite size can be expressed by the following equation (5). β = b - B correct (5) The actual crystallite size L can be calculated using the following equation (6). L = K × λ / (βcos(C / 2)) (6) Here, the constant K is set to 0.9, and λ is the wavelength of the X-rays used in the measurement. C is 2θ, which is the center of the maximum peak position when the peak half-width was calculated above.

[0066] (4) Relative density of 400MPa compacted powder (Measurement of true density) The true density was measured using the gas phase displacement method with He gas (BELMAX, Microtrac Bel). The internal volume of the cell was calculated when the He gas pressure was set to 55 kPa, 60 kPa, 65 kPa, 70 kPa, 75 kPa, 80 kPa, 85 kPa, 90 kPa, 95 kPa, 100 kPa, 105 kPa, and 110 kPa, and the average value was taken as the internal volume of the cell. The cell weight was calculated using an electronic balance. The volume and weight of a blank cell were measured three times using the above method, and the average value was taken as the empty cell volume V1 and the weight as the empty cell weight W1. When the glass solid electrolyte was added to the cell, the volume of the gas phase portion of the cell and the total cell weight were measured three times using the above method, and the average value was taken as the volume excluding the sample V2 and the total cell weight W2. True density d (g / cm³) of glass solid electrolytes 3 The value was calculated using the following formula (7). d = (W2 - W1) / (V1 - V2) (7) The true density of the sample was defined as the average of the true density d calculated three times using the above procedure and formula. The standard deviation of the true density calculated using this method was 0.05 g / cm³. 3 The following applies:

[0067] (Measurement of pellet density) A schematic diagram of the pellet density measuring device is shown in Figure 1. The sample 10 was filled into a cylindrical jig 11 (manufactured by Macol®) and pressurized at 400 MPa using a single-screw press via a stainless steel piston 12. The length L of the apparatus in its blank state (without the sample filled) int And the length L of the apparatus containing the sample after pressurization. after By measuring the height of the sample (pellet) from the difference, the pellet density d can be determined. pellet The result was calculated. Specifically, the diameter of the sample before insertion is 10 mm (cross-sectional area S) pellet :0.785cm 2 A piston 12 was inserted into the cylindrical jig 11 of ). The cylindrical jig 11 was rotated every 90° in a direction perpendicular to the pressurizing direction, and measurements were taken four times. The average value was taken as L. int The measurement was taken in (cm). The measurement was taken while pressurizing the piston 12 by tightening the screw 13 and nut 14 to 8 N·m using a torque wrench. Next, 0.3 g of the glass solid electrolyte powder sample was weighed using an electronic balance and placed into the cylindrical jig 11. After placement, the sample was pressurized by applying pressure to the piston 12 using a single-screw press. The pressure was set to 185 MPa and maintained for 2 minutes, after which the pressure was released. The cell was rotated 120° perpendicular to the pressurizing direction and pressed in the same manner. Then, it was rotated another 120° and pressed in the same manner. Next, the pressure was set to 400 MPa, and the sample was pressurized in the same manner as at 185 MPa. After molding, L int The same procedure was used to take four measurements, and the average value was taken as L after (cm) was used. Pellet density d pellet This was calculated using the following formula (8). d pellet =0.3 / {(L after -L int )×S pellet (8)

[0068] (Calculation of relative density) The calculation was performed using the following formula (9). Relative density (%) = Pellet density × 100 / True density (9)

[0069] (5) Ionic conductivity From the glass solid electrolytes manufactured in each example, a diameter of 10 mm (cross-sectional area S: 0.785 cm²) was obtained. 2 ), circular pellets with a height (L) of 0.1 to 0.3 cm were formed as samples. Electrode terminals were taken from the top and bottom of the samples, and measurements were taken at 25°C using the AC impedance method (frequency range: 5 MHz to 0.5 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency region, the real part Z'(Ω) at the point where -Z''(Ω) is minimized was taken as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(S / cm) was calculated according to the following formula. R = ρ(L / S) σ = 1 / ρ

[0070] (6)ICP measurement The powder of the solid electrolyte prepared in each example was weighed and collected in a vial under an argon atmosphere. KOH alkaline aqueous solution was added to the vial, and the sample was dissolved while taking care to collect sulfur, and then diluted as appropriate to prepare the measurement solution. This was measured using a Paschenrunge-type ICP-OES instrument (SPECTRO ARCOS, SPECTRO Corporation) to determine its composition. Calibration curve solutions were prepared using 1000 mg / L standard solutions for ICP measurement for Li, P, and S, and 1000 mg / L standard solutions for ion chromatography for Cl and Br. Two measurement solutions were prepared for each sample, and five measurements were taken with each solution. The average value was then calculated. The composition was determined by the average of the measurements from these two solutions.

[0071] Example 1 [Fabrication of glass solid electrolytes] (1) Preparation of glass solid electrolytes 2.366 g of lithium sulfide, 3.815 g of phosphorus pentasulfide, 3.446 g of lithium iodide, and 0.373 g of lithium bromide were weighed out, and 600 g of 10 mm diameter zirconia balls were placed in a 500 mL zirconia pot and sealed. Table 1 shows the molar ratio of the starting materials. Using a planetary ball mill (Fritsch, model P-5), the material was ground (mechanical milling) at room temperature at a rotation speed of 220 rpm for 40 hours to obtain a glass solid electrolyte. Table 1 shows the raw material composition ratio, the molar ratio of each element to phosphorus (P), and the evaluation results.

[0072] Examples 2-19, Comparative Examples 1-10 Glass solid electrolytes were prepared in the same manner as in Example 1, except that the raw material composition ratio was changed as shown in Table 1. The evaluation results are shown in Table 1. Note that in Table 1, the amount of Li3PS4 is set to 100 moles, which corresponds to 150 moles of Li2S4 and 50 moles of P2S5, which are the starting materials. For Examples 7, 14, 16, and Comparative Examples 1 and 7, the molar ratio (X / P) of each element to phosphorus (P) in the glass solid electrolyte was measured by ICP. The results are shown below. Example 7: Li / P=4.4, S / P=3.9, Br / P=0.25, I / P=1.26 Example 14: Li / P=3.9, S / P=3.9, Br / P=0.53, I / P=0.52 Example 16: Li / P=4.0, S / P=4.0, Br / P=1.05 Comparative example 1: Li / P=3.0, S / P=4.0 Comparative example 7: Li / P=4.4, S / P=4.0, I / P=1.52

[0073] [Table 1]

[0074] Figure 2 shows the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 1 to 4. Figure 3 shows the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 5 to 8. Figure 4 shows the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 9 to 13. Figure 5 shows the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 14 and 15. Figure 6 shows the X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 16 to 18. Figure 7 shows the X-ray diffraction pattern of the glass solid electrolyte prepared in Example 19. Figure 8 shows the X-ray diffraction patterns of the glass solid electrolytes prepared in Comparative Examples 1 to 8. Figure 9 shows the X-ray diffraction patterns of the glass solid electrolytes prepared in Comparative Examples 9 and 10. XRD measurement results confirmed that the glass solid electrolytes produced in Examples 1-19 were amorphous, and that the lithium halide raw material was partially crystalline. [Industrial applicability]

[0075] The glass solid electrolyte of the present invention is suitable as a structural material for lithium-ion batteries. Furthermore, the lithium-ion battery of the present invention is suitable for use in information-related equipment and communication equipment such as personal computers, video cameras, and mobile phones, as well as batteries used in vehicles such as electric vehicles.

[0076] Although several embodiments and / or examples of the present invention have been described in detail above, those skilled in the art will find it easy to make many modifications to these exemplary embodiments and / or examples without substantially departing from the novel teachings and effects of the present invention. Accordingly, many of these modifications fall within the scope of the present invention. All references made in this specification and to the application on which the priority claim under the Paris Convention of this application is based are incorporated herein by reference.

Claims

1. It contains lithium, phosphorus, sulfur, and halogens, including at least bromine, as constituent elements. The molar ratio of lithium (Li) to phosphorus (P) (Li / P) is 2.0 to 5.

3. The molar ratio of sulfur (S) to phosphorus (P) (S / P) is 2.0 to 4.

5. The molar ratio (X / P) of the halogen (X) to the phosphorus (P) is 0.7 to 2.

3. A glass solid electrolyte that exhibits a peak originating from lithium bromide in powder X-ray diffraction using CuKα radiation.

2. The glass solid electrolyte according to claim 1, wherein the crystallite size calculated from the peak full width at half maximum of the peak with the highest intensity among the peaks derived from lithium bromide is 3 to 60 nm.

3. The halogen contains iodine, The glass solid electrolyte according to claim 1, which exhibits a peak originating from lithium iodide in powder X-ray diffraction using CuKα rays.

4. The glass solid electrolyte according to claim 3, wherein the crystallite size calculated from the peak full width at half maximum of the peak with the highest intensity among the peaks derived from lithium iodide is 3 to 60 nm.

5. The glass solid electrolyte according to claim 1, wherein the relative density of the 400 MPa compacted powder is 90% or more.

6. True density is 2.0–3.0 g / cm³ 3 The glass solid electrolyte according to claim 1.

7. The glass solid electrolyte according to claim 1, wherein the molar ratio (X / P) is greater than 0.

75.

8. The glass solid electrolyte according to claim 1, wherein the molar ratio (X / P) is greater than 0.

86.

9. The halogen contains iodine, The molar ratio of iodine (I) to phosphorus (P) (I / P) is 2.0 or less. The glass solid electrolyte according to claim 1, wherein the molar ratio of bromine (Br) to phosphorus (P) (Br / P) is 0.01 to 1.

5.

10. The glass solid electrolyte according to claim 1, wherein the ionic conductivity is 1 mS / cm or more.

11. A lithium-ion battery comprising a glass solid electrolyte according to any one of claims 1 to 10.

12. A combination of two or more compounds or elements containing lithium, phosphorus, sulfur, and a halogen containing at least bromine as constituent elements, A method for producing a glass solid electrolyte, comprising vitrifying a mixture prepared by adjusting the molar ratio of lithium (Li) to phosphorus (P) (Li / P) to 2.0 to 5.3, the molar ratio of sulfur (S) to phosphorus (P) (S / P) to 2.0 to 4.5, and the molar ratio of halogen (X) to phosphorus (P) (X / P) to 0.7 to 2.3.

Citation Information

Patent Citations

  • Photo sensitive material

    JP1978049427A

  • Electrically connecting device

    JP1980021899A

  • Nuclear reactor emergency shutdown device

    JP1982057284A

  • Manufacturing method of solid electrolyte

    JP2017010936A

  • Sulfide solid electrolyte

    JP2018045997A